2019
DOI: 10.1103/physrevd.99.103501
|View full text |Cite
|
Sign up to set email alerts
|

Entropy methods for CMB analysis of anisotropy and non-Gaussianity

Abstract: In recent years, high-resolution cosmic microwave background (CMB) measurements have opened up the possibility to explore statistical features of the temperature fluctuations down to very small angular scales. One method that has been used is the Wehrl entropy, which is, however, extremely costly in terms of computational time. Here, we propose several different pseudoentropy measures (projection, angular, and quadratic) that agree well with the Wehrl entropy, but are significantly faster to compute. All of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In the following section we will first present a toy model (that may be of interest in its own right) and then show how to reformulate Lieb's conjecture in terms of quantum channels. Here we follow an approach (Schupp 2008 unpublished and [19]) that makes it fairly easy to see how the quantum coherent operators (covariant quantum channels) introduced in [15] arise that were then eventually used in the proof of the conjecture and its generalizations [16,17]. Given the quantum channel we then sketch the beautiful proof of Lieb and Solovej for symmetric 𝑆𝑈 (𝑁) coherent states.…”
Section: Spin Coherent Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the following section we will first present a toy model (that may be of interest in its own right) and then show how to reformulate Lieb's conjecture in terms of quantum channels. Here we follow an approach (Schupp 2008 unpublished and [19]) that makes it fairly easy to see how the quantum coherent operators (covariant quantum channels) introduced in [15] arise that were then eventually used in the proof of the conjecture and its generalizations [16,17]. Given the quantum channel we then sketch the beautiful proof of Lieb and Solovej for symmetric 𝑆𝑈 (𝑁) coherent states.…”
Section: Spin Coherent Statesmentioning
confidence: 99%
“…Let us return to the Wehrl entropy of spin coherent states; closely following [19,25], we shall see how it is related to the quantum coherent operators (covariant quantum channels) introduced in [15]. Let 𝜌 be a density matrix on [𝑙] = C 2𝑙+1 and introduce an ancilla Hilbertspace [ 𝑗] = C 2 𝑗+1 .…”
Section: Projection Entropymentioning
confidence: 99%
See 1 more Smart Citation
“…1000 (entropies). 6,8 In Fig. 1 we compare S ang (8)(10), -S || (13), and S || D (15) with the Solar Dipole as a given physical direction D using the NILC 2015 full sky map.…”
Section: Application To Data Analysismentioning
confidence: 99%
“…It has been in debate for several years by using the CMB data. Numerous research suggested that the CMB data are either non-Gaussian or cannot be accurately described by statistical or mathematical models with few constant parameters, see [16,17,18,19,20,21]. The classical book by Weinberg [22] explained that this anisotropy in the plasma universe was significant enough to produce anisotropy in current galaxy distributions.…”
Section: Introductionmentioning
confidence: 99%